A hybrid dynamic economic environmental dispatch model for balancing operating costs and pollutant emissions in renewable energy: A novel improved mayfly algorithm. (1st October 2022) - Li, Ling-Ling; Lou, Jia-Le; Tseng, Ming-Lang; Lim, Ming K.; Tan, Raymond R.
Graphical abstract: Highlights: This study establishes a dynamic economic environmental dispatch model. A novel IMA algorithm is proposed to solve economic environment dispatch problem. A control strategy is studied to assure the stability of renewable energy output. This study contributes to improve economic and environmental benefits of grid. Abstract: This study proposes a hybrid dynamic economic environmental dispatch model combining thermal power units, wind turbines, photovoltaic and energy storage device to achieve the balance between operating costs and pollutant emissions under the premise of stabilizing the output of renewable energy. Most studies have addressed economic and environmental issues to optimize dispatch as more and more renewable energy is connected to the grid, while ignoring the stability of renewable energy output. Aiming to solve the problem of instability of renewable energy output, a wind-photovoltaic stable output strategy is proposed, and an energy storage device is used to control the dispatched power of renewable energy. The fitness function is improved and an improved mayfly (IMA) algorithm using chaotic initialization, inertia weight and mutation strategy is proposed to find the optimal solution, and the performance of the algorithm is verified on two systems with different configurations. In addition, constraints such as the power balance, output of each power generation device and energy storage device are considered. The results show that the operating costs of the IMA algorithm is 4.12%, 13.21% and 15.14% lower than those of the MA, MFO and PSO algorithms, and the proposed model using the IMA algorithm can effectively achieve the balance between economy and environment and obtain stable renewable energy output. This study provides a useful reference for the stable operation of power grid under a variety of renewable energy access conditions.